Anabolic steroid use in weightlifters and bodybuilders: An internet survey of drug utilization - Perry, P.; Lund, B.; Deninger, M.; Kutscher, E.; Schneider, J. (Clinical Journal of Sport Medicine, 2005)
Purpose: Dietary supplements and ergogenic agents, including anabolic steroids, are common components of present-day bodybuilder and weightlifter training regimens. Prior reports of anabolic steroid use suggest polypharmacy and high doses of injectable agents.